Covid-19 as a Social Crisis and Justice Challenge for Cities - Haase, Annegret (Frontiers in Sociology, 2020)
The perspective deals with Covid-19 as a social crisis and justice challenge for cities. It describes how Covid-19 puts the spotlight on the uneven distribution of goods and burdens, chances and resources that we find in most of the world’s cities today; inequality and justice challenges arise from both the crisis itself and some policy reactions to it as the stay-home policy and economic lockdown. It shows how exposure and vulnerability towards Covid-19 emerges mainly at the intersection of different dimensions of disadvantage and marginalization. The example of housing and green space provision is being used as an example to discuss the general argument in more detail. The perspective concludes, among others, that, in order to overcome the identified social crisis and justice challenge through Covid-19, we have to tackle underlying structures/mechanisms leading to inequitable outcomes in today’s cities and to re-think the social and justice yardsticks of current urban sustainability and resilience debates and strategies.